"Not From Their Culture": The Influence of Artisanal Promotion Agents in the Production and Commercialization of Indigenous Crafts in Chaco, Argentina. (27th May 2022) - Perret, Myriam Fernanda
Abstract: Based on ethnographic fieldwork between August 2012 and August 2018, this article explores the influence of artisanal promotion agents on the woven crafts of Chaco, Argentina. The influence of artisanal promotion agents (APAs) is decisive and heterogeneous – they play a significant role in influencing the craftspersons' decisions about what they make for sale. Built on presumptions of what is inherent to the culture of the Chaco weavers, APAs make suggestions as to the colors, materials and shapes adopted by the craftspeople. In the case of colour, the influences of the agents go unnoticed, but in regards to the shape, their advice has been significant. This article explores how APAs communicate their suggestions to craftspeople through images and prototypes, simultaneously managing the capacity to diversify production and maximise commercial impact. Those who manage these record/communication systems have great influence on the production and commercialization of crafts.